Pelaksanaan Restorative Justice dalam Penegakan Hukum Pidana Anak terhadap Aksi Kriminal dan Teror Senjata Tajam oleh Anak Anggota Kelompok Gangster: (Studi Di Polrestabes Surabaya) - R. Rachmadani Arya Wirawibawa; Hervina Puspitosari (CV Rewang Rencang, 2025)
The existence of the principle of restorative justice in the juvenile criminal justice system in Indonesia has been realized by the diversion process in practice, not all juvenile criminal cases can be pursued and diversioned, because they do not meet the criteria for the conditions for diversion, including in handling cases against children members of gangster groups at the investigation level. Gangster groups consisting of many children often commit various criminal acts, so foresight is needed in law enforcement, especially the imposition of article threats during investigations. In addition, in practice, of course, there are obstacles that must be faced in optimizing diversion for the children of members of gangster groups at the investigation level.